Analisis Sistem Informasi Akuntansi Menggunakan System Usability Scale (SUS) pada BAZNAS Indonesia - Pangestuti, Dinik Fitri Rahajeng; Pinasti, Setyo (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to identify issues in the BAZNAS Indonesia Accounting Information System, SIMBA, used to assist the accounting process for zakat collection and reporting. The research method used was content analysis, which involved distributing an online System Usability (SUS) questionnaire. The results showed that the SIMBA application received a SUS score of 70, indicating that its usability was considered good or acceptable by users, but still marginal. It had a C-grade scale and an OK (good) rating with a percentile rank of 57. This score was supported by respondents' explanations that the SIMBA application generally had a relatively complex usability level and required extensive learning before use.